The Principle “Hardship Begets Ease” And Its Impact On Supporting Neonatal Food Security Policies: An Applied Jurisprudential Study - Abdullah Al-Qathami, Eman Mohammed (Journal of Neonatal Surgery, 2025)
This study aims to present an applied jurisprudential approach to the Islamic legal maxim “hardship begets ease” by linking it directly to the field of food security for newborns, who represent the most vulnerable demographic in terms of medical and religious needs. The study is grounded in real-world challenges related to malnutrition and resource scarcity, and investigates the potential of employing this legal principle to overcome legislative and administrative barriers that hinder the provision of safe and sufficient nutrition for this group. An integrative methodology combining jurisprudential analysis, comparative evaluation between Islamic and Western medical ethics, and inductive examination of contemporary applications in agriculture, food manufacturing, and distribution within Islamic contexts was employed. The study concludes that the principle of ease is not merely a theoretical legal foundation but a flexible legislative gateway that can substantively support food and health policies targeting newborns, especially in situations of necessity, limited resources, or humanitarian crises. It recommends the development of a practical jurisprudential-medical guide to assist policymakers in identifying legitimate circumstances for applying ease within defined limits that ensure public benefit without compromising Islamic legal rulings. It also calls for enhanced coordination between health ministries and juristic bodies to ensure religiously appropriate responses to contemporary nutritional challenges.